Kinetic analysis of a Michaelis-Menten mechanism in which the enzyme is unstable. - Garrido-del Solo, C (1993)
A kinetic analysis of the Michaelis-Menten mechanism is made for the cases in which the free enzyme, or the enzyme-substrate complex, or both, are unstable, either spontaneously or as a result of the addition of a reagent. The explicit time-course equations of all of the species involved has been derived under conditions of limiting enzyme concentration. The validity of these equations has been checked by using numerical simulations. An experimental design and a kinetic data analysis allowing the evaluation of the parameters and kinetic constants are recommended.